Urgensi Larangan Penggunaan Senjata Kimia di Suriah menurut The Chemical Weapon Convention 1993 - Ananda, Ar Raffi Ridho; Kusniati, Retno (Faculty of Law, Universitas Jambi, 2022)
This study aims to determine and analyze the application of The Chemical Weapons Convention 1993